Evaluating the Link Between Dopaminergic Treatment, Gait Impairment, and Anxiety in Parkinson's Disease. Issue 4 (9th January 2016) - Ehgoetz Martens, Kaylena A.; Ellard, Colin G.; Almeida, Quincy J.
Abstract: Background: Anxiety is the most under‐recognized nonmotor symptom of Parkinson's disease (PD), yet it is unclear whether motor impairment exacerbates anxiety observed in PD, or vice versa. The current study examined: (1) whether movement (i.e., walking vs. standing) elevates distress in PD; (2) how dopaminergic treatment influences anxiety specifically while walking; and (3) whether these responses are worse in PD patients with gait impairments (compared to those without). Methods: Twenty healthy control participants (HC), 17 PD participants without gait impairments (PD‐GI), and 14 PD participants with gait impairments (PD+GI) performed two tasks (stand vs. walk) in two virtual environments: (1) LOW threat; (2) HIGH threat. This protocol was completed in on and off dopaminergic states (to evaluate the effect of exacerbating motor symptoms). Results: PD+GI reported greater levels of anxiety compared to PD‐GI and HC overall. All participants reported greater levels of anxiety and had higher skin conductance levels (SCLs) when walking compared to standing. The HIGH threat condition also generated greater levels of anxiety in all participants, compared to LOW threat, especially when required to walk. Notably, only PD+GI reported greater levels of anxiety when walking compared to standing in the LOW threat environment. Dopaminergic medication reduced self‐reported levels of anxiety, but did not significantly change SCL. Conclusion: This study provides evidence that movement exacerbates anxiety in all older adults, but is particularly influential in those with gait impairments, which emphasizes the importance of optimally treating movement impairments as a method of reducing movement driven anxiety.